Aplikasi Tricoderma sp. dan Streptomyces sp. Terhadap Produksi Bawang Putih (Allium sativum L.) - Dian Utami Zainuddin; Suryani Dewi (Fapetrik-UMPAR, 2020)
This study aims to determine the effect of Trichoderma sp., And Streptomyces sp., On the production of garlic plants. The research objective was to obtain a combination of biological fertilizers, which are suitable for the cultivation of local Indonesian garlic plants. The study was started by making a suspension by taking the inoculant Trichoderma sp., And Streptomyces sp., Using ose, then put it in a liquid medium and incubated for 5 days. Inoculation of Trichoderma sp., And Streptomyces sp., was done by pouring it into the planting hole area of 5 mL each of the garlic plants according to the treatment consisting of control (without suspension); giving suspension of Trichoderma sp .; Suspense Streptomyces sp .; and Trichoderma sp. + Streptomyces sp. Data were analyzed using the F test, treatments that had a real effect were further tested with the Least Significant Difference Test at the 5% level. The results showed that the treatment significantly affected plant height, dry tuber weight, and tuber diameter. The highest average for all observation parameters was found in the fungus Trichoderma sp. + Streptomyces sp., While the lowest average was in the treatment without the fungal suspension for all parameters of the observation.